2023
DOI: 10.1101/2023.09.29.559957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in the urinary proteome of rats after short-term intake of magnesium threonate

Ziyun Shen,
Minhui Yang,
Haitong Wang
et al.

Abstract: Magnesium is an important mineral in living organisms and has multiple functions in the human body, wherein it plays an important therapeutic and preventive role in a variety of diseases. In the present study, urine samples of rats before and after gavage of magnesium threonate were collected, and the urinary proteome was identified using the LC-MS/MS technique and analyzed using various databases. The results illustrated that the urinary proteome of rats was significantly altered after short-term intake of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Our laboratory has previously reported that the urine proteome is able to reflect the effects of magnesium threonate intake on the body in a more systematic and comprehensive manner, with the potential to provide clues for clinical nutrition research and practice [3] . However, to date, there have been no studies exploring the effects of iron on the body from the perspective of the urine proteome.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has previously reported that the urine proteome is able to reflect the effects of magnesium threonate intake on the body in a more systematic and comprehensive manner, with the potential to provide clues for clinical nutrition research and practice [3] . However, to date, there have been no studies exploring the effects of iron on the body from the perspective of the urine proteome.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins in urine contain a wealth of information that can reflect small changes produced in different systems and organs of the organism. Our laboratory has previously reported that the urine proteome can reflect the effects of magnesium threonate intake on the body in a more systematic and comprehensive manner, and has the potential to provide clues for clinical nutrition research and practice [5] . To date, no studies have addressed the effects of complex nutrients on the urinary proteome of healthy adults.…”
mentioning
confidence: 99%